Study the effect of using ultrasonic membrane anaerobic system (umas) in treating sugarcane waste and methane gas production - Ragini , Mahendran (2014)
Sugarcane industry is one of the most important industries in many developing countries. However, sugarcane industry produces significant amount of wastes mainly in the form of liquid wastes. In present study, biological treatment with membrane technology and ultrasound effect was carried out to treat sugarcane wastewater. The main objective of this study is to make an overall comparison between membrane anaerobic system (MAS) and ultrasonic membrane anaerobic system (UMAS) in treating sugarcane waste. Raw sugarcane wastewater was operated in a membrane anaerobic reactor for 5 hours for 7 continuous days. After 5 hours of operation, the permeate (filtrate) from the reactor was collected and tested for BOD, COD, TSS and VSS. The gas produced was collected using designated syringe. The experiment was repeated with 10 kHz of ultrasound frequency devise attached to the membrane to investigate the effect of ultrasonic wave towards the process. From this study, for COD and BOD, MAS has achieved 86% removal efficiency and UMAS achieved 96% removal. For TSS, MAS obtained 81% removal efficiency but UMAS attained 100% removal which shows UMAS has removed all the detectable suspended solids from the wastewater. The same trend goes for VSS removal efficiency. MAS produced 1400mL of permeate and UMAS produced 2346mL of permeate. This huge difference in volume was due to the fouling which blocks the membrane pores. For biogas production, 68% and 77% of methane gas have been produced during MAS and UMAS treatments respectively. From these results, it proves that UMAS has prevented fouling and it is more proficient than MAS as it produced permeate which meet the discharge limit fixed by Malaysia Department of Environmental (DOE)